2019
DOI: 10.1016/j.diagmicrobio.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FTD® respiratory pathogens 33 and a singleplex CDC assay for the detection of respiratory viruses: A study from Cameroon

Abstract: Introduction: This study compares the detection of 14 common respiratory viruses by two different real-time reverse transcription polymerase chain reaction (rRT-PCR) methods: in house singleplex tests developed by the Centers for Disease Control and Prevention and the commercially available Fast Track Diagnostic (FTD®) Respiratory Pathogens 33 multiplex test. Methods: A total of 217 nasopharyngeal swabs were analyzed using CDC singleplex rRT-PCR and FTD® Respiratory Pathogens 33 multiplex assays, for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For a few patients, pleural effusion and endotracheal aspirate samples were collected. A total of 200 µl samples were used for nucleic acid extraction as previously reported by using easyMAG (bioMerieux, Marcy l’Etoile, France) [ 9 , 12 , 13 ]. Thirty-three respiratory pathogens were detected by using the multiplex real-time PCR method (Fast Track Diagnostic, Junglinster, Luxembourg), including IFVs (A, B and C) and the 2009 subtype of IFVA/H1N1, HPIV 1–4, HCoVs (NL63, 229E, OC43 and HKU1), HMPV A and B, EVs (including HRVs), RSV A and B, Adv, human parechovirus (HPeV), human bocavirus (HBoV), Pneumocystis jirovecii ( P. jirovecii ), M. pneumoniae , Chlamydophila pneumoniae ( C. pneumoniae ), S. pneumoniae , H. influenzae , H. influenzae type b (Hib), Staphylococcus aureus ( S. aureus ), Moraxella catarrhalis ( M. catarrhalis ), Bordetella spp.…”
Section: Methodsmentioning
confidence: 99%
“…For a few patients, pleural effusion and endotracheal aspirate samples were collected. A total of 200 µl samples were used for nucleic acid extraction as previously reported by using easyMAG (bioMerieux, Marcy l’Etoile, France) [ 9 , 12 , 13 ]. Thirty-three respiratory pathogens were detected by using the multiplex real-time PCR method (Fast Track Diagnostic, Junglinster, Luxembourg), including IFVs (A, B and C) and the 2009 subtype of IFVA/H1N1, HPIV 1–4, HCoVs (NL63, 229E, OC43 and HKU1), HMPV A and B, EVs (including HRVs), RSV A and B, Adv, human parechovirus (HPeV), human bocavirus (HBoV), Pneumocystis jirovecii ( P. jirovecii ), M. pneumoniae , Chlamydophila pneumoniae ( C. pneumoniae ), S. pneumoniae , H. influenzae , H. influenzae type b (Hib), Staphylococcus aureus ( S. aureus ), Moraxella catarrhalis ( M. catarrhalis ), Bordetella spp.…”
Section: Methodsmentioning
confidence: 99%
“…Such panels would also permit data to be generated on potential non-TB causes of disease. Several multi-pathogen diagnostic panels like FilmArray Respiratory Panel (Biofire Diagnostics), the Respiratory Multi Well System MWS r-gene Range (BioMerieux), FTD 21, and FTD 33 respiratory panels (FTD), Respiratory Pathogen ID/AMR Panel (Illumina) are potential candidate technologies; however, further development and research is warranted to simplify these tests and make them more useful for the types of populations in which investigations for TB are frequent [ 109 ].…”
Section: Confirmatory Toolsmentioning
confidence: 99%
“…Other studies have reported on sensitivity and specificity or concordance of the FTD-33 assay compared with either other multipathogen platforms or in-house singleplex tests. [8][9][10][11][12][13] Most of these studies reported comparable results for the influenza A, influenza B, and H1N1 assays; however, two reported significant discrepancies with the influenza B assay. 8,10 Most specimens with discordant results had higher ct values, closer to the limit of detection; thus, discordant results were not unexpected given the lower concentrations of virus in the specimens.…”
Section: Discussionmentioning
confidence: 98%